Should Global Englishes be taught? Perceptions from Chinese English teachers in Middle school education - Yajing Fu (Cogent Education, 2024)
This qualitative research explores 10 Chinese middle school teachers’ perceptions of English and English teaching concerning Global Englishes (GE) and the feasibility of incorporating GE into English language education. Through semi-structured interviews and thematic analysis within the framework of 2018 Global English Language Teaching (GELT), the research findings showed that teachers’ perceptions of English were globally defined, and they believed that English users with diverse linguistic and social backgrounds across the globe serve as the foundation for its usage. Regarding its pedagogical implementation, most participants questioned the appropriateness of non-native English in teaching and viewed native English as the most suitable approach in ELT, especially in assessment. However, some participants questioned the conventional ideology of native English standardisation, favouring cultural exchange and mutual intelligibility above the rigorous fixation on grammatical correctness to better equip students for the current English diversity. The contrasting views highlight the need to balance standardisation and linguistic diversity in ELT by finding a middle ground. This paper suggests that ELT stakeholders adopt an inclusive and flexible multicompetence approach with a shifting focus on practical skills and communication effectiveness in curricula design, assessment and classroom activities to better address the needs of English language learners in global contexts.